Oral mucositis: recent perspectives on prevention and treatment - Paulo Sérgio da Silva Santos; Ana Cristina Messaggi; Andrea Mantesso; Marina Helena Cury Gallotini de Magalhães (Faculdade São Leopoldo Mandic, 2009)
Oral mucositis is a result of toxicity and one of the most common side effects of radiotherapy and chemotherapy in cancer treatment and in hematopoietic stem cell transplantation. Clinically these changes are characterized by epithelial atrophy, edema, erythema and the appearance of ulcerations that can affect the entire oral mucosa, causing pain and discomfort, impairing speech, and swallowing food. In addition to the major symptoms, the ulcers increase the risk of local and systemic infection, compromising function and interfering with oral antineoplastic treatment and may lead to it being discontinued. The diagnosis, prevention and therapeutic strategies in providing support in cases of oral mucositis are the dentist's responsibility. Through critical analysis of literature, the aim of this article is to present oral mucositis, its pathogenesis, clinical features and treatments offered today to address or control the condition, highlighting the importance of dentists' role in its management.